2017
DOI: 10.1590/0103-6440201701430
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity Evaluation of Root Canal Sealers Using an In Vitro Experimental Model with Roots

Abstract: The aim of the present study was to evaluate the cytotoxicity of root canal sealers under conditions closely resembling a clinical reality. A primary human fibroblast cell line was seeded in 24-well acrylic plates with Dulbecco's modified Eagle's medium supplemented with 10% serum fetal bovine (SFB) and incubated for 24 h. Root canals from premolars were filled and individually attached to nylon devices to be stabilized in the wells with the already seeded cells. Specimens were divided into groups as follows: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
2
10
0
4
Order By: Relevance
“…Calcium silicate-based sealers have been proposed in endodontics due to their biological properties. MTA Fillapex® (Angelus, Londrina, PR, Brazil), although including mineral trioxide aggregate (MTA) and presenting low toxic effects (11), this material is also a resin-based sealer and its main chemical component is salicylate resin. MTA Fillapex exhibits high solubility and dimensional change (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Calcium silicate-based sealers have been proposed in endodontics due to their biological properties. MTA Fillapex® (Angelus, Londrina, PR, Brazil), although including mineral trioxide aggregate (MTA) and presenting low toxic effects (11), this material is also a resin-based sealer and its main chemical component is salicylate resin. MTA Fillapex exhibits high solubility and dimensional change (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Em relação ao método de avaliação da citotoxicidade dos cimentos MTA Fillapex e AH Plus, o mais utilizado foi o método de ensaio do Brometo 3-[4,5-dimetil-tiazol-2-il]-2,5 difeniltetrazólio (MTT) -que é um ensaio colorimétrico, versátil e quantitativo que mede apenas a atividade das enzimas presentes nas células vivas e pode ser lido rapidamente num leitor ELISA 11,13,14,17,27,28,33 Ao contrário do MTA Fillapex, cuja toxicidade não diminuiu ao longo dos períodos de tempo testados, o cimento AH Plus, quando recém misturado foi citotóxico, porém, ao decorrer dos dias após a mistura, o cimento AH Plus já não apresentou nenhum efeito citotóxico 11,14,15,16,31 . Tal característica, está de acordo com estudos anteriores 22,23 , que documentaram o efeito citotóxico moderado a grave do AH Plus imediatamente após a mistura.…”
Section: Discussionunclassified
“…Among the resin sealers available for endodontic use, the AH Plus sealer was selected because significant evidence supports its use for filling the root canal system owing to its high flow rate and low solubility after the final setting (Torres et al, 2020). However, its cytotoxicity is attributed to the release of formaldehyde and degradation of amines, which accelerate the polymerization process of the epoxy resin‐based sealer (Lee et al, 2019; Teixeira et al, 2017). Sealer 26 is also an epoxy resin‐based sealer, but was chosen because it contains calcium hydroxide, as it is observed that this component can interfere with the inflammatory process (Queiroz et al, 2005; Souza et al, 2019; Tanomaru‐Filho et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…AH Plus (Dentsply‐Sirona) is an epoxy resin‐based sealer that has significant evidence supporting its use for root canal filling. However, its cytotoxicity is related to formaldehyde release and amine degradation because of its long setting time (until it achieves complete polymerization) (Teixeira et al, 2017). This inhibits the initial healing capacity of the tissues in contact with this material.…”
Section: Introductionmentioning
confidence: 99%